2021
DOI: 10.21203/rs.3.rs-505666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Adjunctive Traditional Chinese Medicine Therapy on Survival in Primary Liver Cancer: A Real-world Study Based on EMRs

Abstract: BackgroundPrimary liver cancer is a common clinical malignancy. Traditional Chinese medicine (TCM) is an alternative treatment for primary liver cancer. TCM effectively improves the survival rate and quality of life of patients, but high-level evidence is lacking.Patients and methodsThis study determined whether the combination of TCM and conventional cancer treatment affects the survival of liver cancer patients. Patients were selected from 5 tertiary hospitals in Henan Province. Two thousand and sixty-seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Recently, increasing real-world data have suggested that TCM has evident benefits in cancer treatment in terms of improving quality of life (Tang et al, 2019) and prolonging survival (Shih et al, 2021). The data include benefits on ovarian cancer (Zhu et al, 2019), advanced liver cancer (Zhao et al, 2021), and PC (P. H. Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing real-world data have suggested that TCM has evident benefits in cancer treatment in terms of improving quality of life (Tang et al, 2019) and prolonging survival (Shih et al, 2021). The data include benefits on ovarian cancer (Zhu et al, 2019), advanced liver cancer (Zhao et al, 2021), and PC (P. H. Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing real-world data have suggested that TCM has evident benefits in cancer treatment in terms of improving quality of life ( Tang et al, 2019 ) and prolonging survival ( Shih et al, 2021 ). The data include benefits on ovarian cancer ( Zhu et al, 2019 ), advanced liver cancer ( Zhao et al, 2021 ), and PC ( P. H. Lin et al, 2019 ). However, the anti-tumor use of TCM is not simply to pile up anti-tumor drugs, but to use drugs under the guidance of the Chinese medicine theory, and this aspect is rarely reported.…”
Section: Discussionmentioning
confidence: 99%